PENGARUH KERAGAMAN PRODUK, KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO KELAPA AGUNG I DI LAMONGAN SITUBONDO - Ediyanto, Ediyanto; Minullah, Minullah; Makrifa, Septiatul (Relawan Jurnal Indonesia, 2024)
This study aims to determine the effect of product diversity, service quality and location variables partially on purchasing decision variables, to determine the effect of variable product diversity, service quality and location simultaneously on purchasing decision variables, to determine the effect of variables Product diversity, service quality and location were dominant in purchasing decision variables. The result of this research is multiple linear regression equation, namely Y = -6,909E-16 + 0,208X1 + 0,576X2 + (-0,124X3) + e. Partially product diversity has a significant positive effect with a value of 2.201, amounting to 1.985. Service quality has a significant positive effect with a value of 5.595, 1.985 and location has a significant positive effect with a value of -1.252, of -1.985. Simultaneously, the variable product diversity, service quality and location have an effect on purchasing decisions with a value of 21.574, amounting to 2.70. The variable with the most dominant influence in this study is the quality of service with a value of 5.595.